1999
DOI: 10.1001/jama.282.3.267
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacist Participation on Physician Rounds and Adverse Drug Events in the Intensive Care Unit

Abstract: The presence of a pharmacist on rounds as a full member of the patient care team in a medical ICU was associated with a substantially lower rate of ADEs caused by prescribing errors. Nearly all the changes were readily accepted by physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
843
9
57

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,367 publications
(950 citation statements)
references
References 11 publications
(15 reference statements)
41
843
9
57
Order By: Relevance
“…The majority of the studies have been conducted in North America, but similar beneficial results have been published from studies conducted in Asia [4,8,9], the Middle East [10], and Europe [11]. Provision of drug information, clarifying and correcting medication orders, identifying drug interactions as well as actual or potential adverse drug events, and recommending alternative therapies account for greater than 90 % of ICU pharmacists' activities [3,4,8,13,14]. The studies indicate that a large majority, and in most studies almost all, of pharmacists' recommendations are accepted by the physicians [3,4,[13][14][15].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The majority of the studies have been conducted in North America, but similar beneficial results have been published from studies conducted in Asia [4,8,9], the Middle East [10], and Europe [11]. Provision of drug information, clarifying and correcting medication orders, identifying drug interactions as well as actual or potential adverse drug events, and recommending alternative therapies account for greater than 90 % of ICU pharmacists' activities [3,4,8,13,14]. The studies indicate that a large majority, and in most studies almost all, of pharmacists' recommendations are accepted by the physicians [3,4,[13][14][15].…”
mentioning
confidence: 93%
“…In fact, within the SCCM guidelines for best practice model and ICU staffing [2], pharmacist presence was considered as best practice supported by grade C evidence, the highest level of all recommendations in that document. A summary of the studies evaluating the impact of having a dedicated pharmacist in the ICU is shown in [3] clearly demonstrated that presence of pharmacists in a medical ICU reduced medication errors and cost. These benefits appear generalizable since the studies have been conducted in a variety of ICUs (e.g., medical, surgical, neurosurgical, cardiac, and pediatric) using different physician staffing models (e.g., open vs closed ICU), and date back to the early 1990s [13].…”
mentioning
confidence: 99%
“…In order to be successful, these initiatives must be designed and implemented through organizational support structures and institutionalized through enhanced education, training, and implementation of information technology that improves work force capabilities [30,31]. For example, Brigham and Women's Hospital was able to reduce the adverse drug event (ACE) rate in the intensive care unit (ICU) by two-thirds by implementing information technology and by having clinical pharmacists participate in patient care with the ICU team [32].…”
Section: Limitations Of Current Researchmentioning
confidence: 99%
“…A list of alerts concerning potential or actual ADEs is automatically generated for care givers. Another example is the assignment of clinical pharmacists to patient care teams [32].…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation